Review of Apoplophora (Acari: Oribatida: Mesoplophoridae), with the description of a new species from China - Liu, Dong; Chen, Jun; Qiao, Gexia (Zootaxa, 2009)
The oribatid mite genus Apoplophora Aoki, 1980 (Mesoplophoridae) is reviewed, and a checklist and key to all known species are provided. Three species of Apoplophora including a new species, Apoplophora dentata sp. nov. from Tibet, and a newly recorded species from China, Apoplophora heterotricha Mahunka, 1987, are identified, and their morphological descriptions and illustrations are also given.